2018
DOI: 10.1002/rem.21577
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of As, Cd, Co, Cr, Cu, Pb, Ni, and Zn at the soil/plant interface around an uncontrolled landfill (Casablanca, Morocco)

Abstract: The present work undertaken in the environmental context aims to study the distribution of heavy metals in plants that grow naturally around uncontrolled landfills. The study's goal was to identify plants that can be used to remediate contaminated soils. For this purpose, 14 plants species and their rhizospheric soil samples were collected and analyzed for arsenic, cadmium, cobalt, chromium, copper, lead, nickel, and zinc by inductively coupled plasma‐atomic emission spectrometry. The results showed the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…This native plant species with both the capacity to accumulate high amounts of Cd in its roots and high biomass production could be used to minimize the migration of Cd in soil. This process reduces metal mobility and leaching towards groundwater's [74].…”
Section: Heavy Metals Concentration In Plantsmentioning
confidence: 99%
“…This native plant species with both the capacity to accumulate high amounts of Cd in its roots and high biomass production could be used to minimize the migration of Cd in soil. This process reduces metal mobility and leaching towards groundwater's [74].…”
Section: Heavy Metals Concentration In Plantsmentioning
confidence: 99%
“…It extends over 70 hectares and receives 5000 tons/day of waste. This landfill was opened in 1986, and until today, it receives waste from the whole of Casablanca, which contains domestic, industrial, medical, and hospital waste discharged directly without prior treatment [16,20]. Around 3500 tons of domestic waste reached the Médiouna landfill by 750 garbage compactor trucks and discharged into the trash mound that currently reached 50m in height, while 3000 tons of industrial and hospital waste without pretreatment are daily discharged also in the landfill [33].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The possible impact of the huge amount of waste dumped in the Médiouna landfill was widely studied but not enough to identify them accurately. The studies carried out in the landfill area, and surrounding areas show evident contamination of groundwater and soil by landfill leachate [16,20]. In addition, the emission of toxic pollutants through the incineration of waste affect the air quality.…”
Section: Pressures (Opportunities and Threats)mentioning
confidence: 99%
See 1 more Smart Citation
“…The successful implementation of phytomanagement techniques should consider several aspects such as plant selection, irrigation, the addition of amendments, fertilization, and stabilization of heavy metals in the plant rhizosphere (Mendez & Maier, 2008). Moreover, in arid and semiarid areas, drought and salt-tolerant native species (Fait et al, 2018), which are naturally adapted to the environment and integrated into the landscape, could be the best candidates (Midhat, Ouazzani, Esshaimi, Ouhammou, & Mandi, 2017). In general, only a few studies have shown the suitability of local plants in Morocco for phytostabilization and, in particular, no previous research has investigated the use of local plants for the phytomanagement of PW applied as an SR cover of sulfide tailings at KAM.…”
Section: Introductionmentioning
confidence: 99%